The effects of differentiation strategies on firm performance: the role of sustainable procurement policies in environmental uncertainty - Arslan, Onur; Can, Esin (EMERALD GROUP PUBLISHING LTD, 2025)
PurposeThe main objective of this paper is to examine the effect of procurement policies within the sustainability framework, which is a key factor influencing enterprise performance. Additionally, the study focuses on the mediating role of sustainable procurement strategies in the performance relationship and the moderating role of environmental uncertainties.Design/methodology/approachTo achieve research objectives, an empirical survey was conducted among 257 mid-level and senior executives in T & uuml;rkiye. CFA and SEM analyses were performed to validate the data and examine the hypothesized relationships.FindingsThe strong impact of differentiation strategies on company performance shows that differentiation strategies provide significant improvements in sub-performance criteria. The positive impact of sustainable procurement policies on performance emphasizes the importance of long-term strategic planning in particular. However, the moderator role of uncertainty exhibits a complex structure and must be validated.Research limitations/implicationsThe research was conducted only on mid-level and senior executive procurement professionals due to their role in strategy determination and implementation. However, the research is a cross-sectional study based on 2022 data.Practical implicationsFirms should reshape their competitive strategies not only to increase market share but also to consider environmental and social sustainability goals. In particular, the integration of differentiation strategies with sustainability principles can provide long-term competitive advantages to businesses.Originality/valueThe key value of this research lies in examining the mediating effects of sustainable procurement policy approaches on the relationship between differentiation and firm performance.
Keywords: Differentiation strategy; Sustainable procurement policies; Uncertainty; Firm performance; SUPPLY CHAIN MANAGEMENT; FINANCIAL PERFORMANCE; COMPETITIVE STRATEGY; IMPACT; FRAMEWORK; Business & Economics